Pengaruh Digitalisasi Perbankan terhadap Loyalitas Nasabah dimediasi Kepuasan Nasabah pada Bank Kalsel Cabang Utama - Tri Utami; Maryono (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2026)
This study aims to test and analyze the significant influence of digital marketing and service quality on customer satisfaction mediated by corporate image at Bank Kalsel Marabahan Branch. This study uses a quantitative research method with an explanatory type and uses the SmartPLS data analysis method. By collecting data through distributing questionnaires to customers of Bank Kalsel Marabahan Branch with a sample of 100 respondents. The results of this study prove that digital marketing does not have a significant effect on customer satisfaction, while service quality and company image have a significant effect on customer satisfaction. Digital marketing and service quality have a significant effect on company image. Digital marketing and service quality have a significant effect on customer satisfaction through company image